High-Resolution Mapping of Transcription Initiation in the Asexual Stages of Toxoplasma gondii - Markus, Benedikt M.; Waldman, Benjamin S.; Lorenzi, Hernan A.; Lourido, Sebastian (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii is a common parasite of humans and animals, causing life-threatening disease in the immunocompromised, fetal abnormalities when contracted during gestation, and recurrent ocular lesions in some patients. Central to the prevalence and pathogenicity of this protozoan is its ability to adapt to a broad range of environments, and to differentiate between acute and chronic stages. These processes are underpinned by a major rewiring of gene expression, yet the mechanisms that regulate transcription in this parasite are only partially characterized. Deciphering these mechanisms requires a precise and comprehensive map of transcription start sites (TSSs); however, Toxoplasma TSSs have remained incompletely defined. To address this challenge, we used 5′-end RNA sequencing to genomically assess transcription initiation in both acute and chronic stages of Toxoplasma. Here, we report an in-depth analysis of transcription initiation at promoters, and provide empirically-defined TSSs for 7603 (91%) protein-coding genes, of which only 1840 concur with existing gene models. Comparing data from acute and chronic stages, we identified instances of stage-specific alternative TSSs that putatively generate mRNA isoforms with distinct 5′ termini. Analysis of the nucleotide content and nucleosome occupancy around TSSs allowed us to examine the determinants for TSS choice, and outline features of Toxoplasma promoter architecture. We also found pervasive divergent transcription at Toxoplasma promoters, clustered within the nucleosomes of highly-symmetrical phased arrays, underscoring chromatin contributions to transcription initiation. Corroborating previous observations, we asserted that Toxoplasma 5′ leaders are among the longest of any eukaryote studied thus far, displaying a median length of approximately 800 nucleotides. Further highlighting the utility of a precise TSS map, we pinpointed motifs associated with transcription initiation, including the binding sites of the master regulator of chronic-stage differentiation, BFD1, and a novel motif with a similar positional arrangement present at 44% of Toxoplasma promoters. This work provides a critical resource for functional genomics in Toxoplasma, and lays down a foundation to study the interactions between genomic sequences and the regulatory factors that control transcription in this parasite.